MicroRNA let-7a inhibits proliferation of human prostate cancer cells in vitro and in vivo by targeting E2F2 and CCND2. - Qingchuan Dong (Public Library of Science (PLoS), 2010)
Background Previous work has shown reduced expression levels of let-7 in lung tumors. But little is known about the expression or mechanisms of let-7a in prostate cancer. In this study, we used in vitro and in vivo approaches to investigate whether E2F2 and CCND2 are direct targets of let-7a, and if let-7a acts as a tumor suppressor in prostate cancer by down-regulating E2F2 and CCND2. Methodology/principal Findings Real-time RT-PCR demonstrated that decreased levels of let-7a are present in resected prostate cancer samples and prostate cancer cell lines. Cellular proliferation was inhibited in PC3 cells and LNCaP cells after transfection with let-7a. Cell cycle analysis showed that let-7a induced cell cycle arrest at the G1/S phase. A dual-luciferase reporter assay demonstrated that the 3'UTR of E2F2 and CCND2 were directly bound to let-7a and western blotting analysis further indicated that let-7a down-regulated the expression of E2F2 and CCND2. Our xenograft models of prostate cancer confirmed the capability of let-7a to inhibit prostate tumor development in vivo. Conclusions/significance These findings help to unravel the anti-proliferative mechanisms of let-7a in prostate cancer. Let-7a may also be novel therapeutic candidate for prostate cancer given its ability to induce cell-cycle arrest and inhibit cell growth, especially in hormone-refractory prostate cancer.